The effects of oxygen vacancies on ferroelectric phase transition of HfO2-based thin film from first-principle - Zhou, Y.; Zhang, Y.K.; Yang, Q.; Jiang, J.; Fan, P.; Liao, M.; Zhou, Y.C. (Computational materials science, 2019)
[Display omitted] The newly discovered hafnium oxide (HfO2)-based ferroelectric film shows many advantages over the traditional perovskite films in the application of information storage. However, the mechanism of ferroelectric phase transition of the HfO2-based film is still confusing to the researchers. Here, the effects of oxygen vacancies and the complex defects formed by the combination of oxygen vacancies and typical impurity elements on ferroelectric phase transition and polarization performance of HfO2 were systematically investigated by first-principle calculation. Due to the ambiguous effects of electrode/ferroelectric interfaces on the ferroelectricity of HfO2-based film, the influence of oxygen vacancies at the TiN/HfO2 interface was also studied. It was found that the oxygen vacancies, and impurities N and La, which would form defect dipoles by combining with oxygen vacancies and induce a local build-in bias, would promote the ferroelectric phase transition in the bulk of HfO2-based film. Additionally, oxygen vacancies, which are inclined to migrate to the interface, would cause the transition of the interfacial tetragonal phase to the ferroelectric phase, and then to the monoclinic phase. This result may be helpful for the understanding of the origin of ferroelectricity as well as the mechanisms of wake-up and fatigue effects of HfO2-based ferroelectric film.